2014
DOI: 10.3389/fnhum.2014.00141
|View full text |Cite
|
Sign up to set email alerts
|

Who is going to walk? A review of the factors influencing walking recovery after spinal cord injury

Abstract: The recovery of walking function is considered of extreme relevance both by patients and physicians. Consequently, in the recent years, recovery of locomotion become a major objective of new pharmacological and rehabilitative interventions. In the last decade, several pharmacological treatment and rehabilitative approaches have been initiated to enhance locomotion capacity of SCI patients. Basic science advances in regeneration of the central nervous system hold promise of further neurological and functional r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(113 citation statements)
references
References 97 publications
(163 reference statements)
2
90
0
9
Order By: Relevance
“…Less than 10% of patients reaching complete FI had a motor-complete SCI (AIS A or B) which supports previous work suggesting that the severity of the SCI is the main and most consistent predictor of functional recovery [1,10,13]. Individuals with a motor-incomplete SCI generally present significant higher neurological and functional recovery in comparison with motor-complete SCI [14][15][16]. Accordingly, the logistic regression analyses showed that patients with incomplete SCI (AIS B, C or D) were more likely to reach complete FI (odds ratios between 10 and 264) as compared to patients with a complete AIS A cervical SCI.…”
Section: Discussionsupporting
confidence: 85%
“…Less than 10% of patients reaching complete FI had a motor-complete SCI (AIS A or B) which supports previous work suggesting that the severity of the SCI is the main and most consistent predictor of functional recovery [1,10,13]. Individuals with a motor-incomplete SCI generally present significant higher neurological and functional recovery in comparison with motor-complete SCI [14][15][16]. Accordingly, the logistic regression analyses showed that patients with incomplete SCI (AIS B, C or D) were more likely to reach complete FI (odds ratios between 10 and 264) as compared to patients with a complete AIS A cervical SCI.…”
Section: Discussionsupporting
confidence: 85%
“…Other than the 2 patients 51 and 64 years of age, the remaining patients were in their 20s and 30s, which might have contributed to a better outcome in the study. 14 We again applaud the authors' effort in conducting such research with the hope of improving patient outcome after SCI. While hypothermia may have a significant impact on improving the clinical outcome in patients with complete SCI, the generalizability of this study is severely limited by the lack of control group and various aforementioned confounding factors.…”
Section: Hypothermia For Spinal Cord Injurymentioning
confidence: 98%
“…2,14,15,17,22 We have reported our technique and clinical data on the outcome and safety profile of modest systemic hypothermia for 48 hours after cervical AIS Grade A SCI. 1,5,6,13,15 In our initial study, 6 of the 14 patients (42.8%) improved one AIS grade or better.…”
Section: Hypothermia For Spinal Cord Injurymentioning
confidence: 99%
“…Ancak egzersiz yoğunluğunun fazlalığı veya tek başına sık tekrarlı egzersizler ideal motor öğrenme için yeterli değildir. Santral sinir sistemi plastisitesi için sık tekrarlı görev spesifik terapilere ihtiyaç vardır (22,23).…”
Section: Lokomotor Egzersizlerunclassified